DIGITAL PARENTING: POLA ASUH MENDIDIK ANAK USIA 5-6 TAHUN DI DESA MAMPANG KECAMATAN KOTAPINANG KABUPATEN LABUHANBATU SELATAN - Luluk Indriyanti; Kamtini (CV. ADIBA AISHA AMIRA, 2025)
This research aims to understand the implementation of digital parenting: a nurturing pattern for children aged 5-6 years in Mampang Village, Kotapinang District, Labuhanbatu Selatan Regency. The method used in this study is qualitative research. Data collection was conducted through observation, interviews, and documentation. Data analysis in this study uses three stages: data collection, data reduction, and data presentation. The validity of the data is ensured through triangulation techniques. Based on the results of data analysis in this research, of the five parents who were the subjects of the study, the digital parenting styles applied by these parents were different. This study describes how parents set the time for giving gadgets to their children, the duration allowed for children to play with gadgets, and the content that may be watched by the children.